120th Birth Anniversary of the Writer Ieva Simonaitytė: Memory, Heritage, and Communication - Kaunas, Domas (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]The subject of research is the experience and results of the commemoration of the 120th birth anniversary of the writer Ieva Simonaitytė (1897–1978). The significance of this event, celebrated on the national scale, like other anniversaries of prominent personalities in Lithuanian history, was validated by the decision of the Seimas of the Republic of Lithuania and by the 2017 State program,approved by the Prime Minister. Such a decision meant that the State pledged itself to highlight the writer‘s humanistic values and her creative heritage. The aims of research were to determine the initiatives of the writer’s anniversary commemoration, the most important documents and the objectives raised in them, the process of their realization, the achievements and the content. According to the collected data, the events commemorating Ieva Simonaitytė‘s anniversary were held all over Lithuania. However, the most important ones were centred in the writer’s native land – West Lithuania, the former Klaipėda Region. Major events were organized in the cities and towns of Klaipėda, Šilutė, Pagėgiai, Priekulė, Gargždai as the cultural centres of the nearest local authorities. Such an orientation can be explained by the limited budgetary funding of the commemoration program, with scanty allocations mainuly channeled to the region’s libraries, museums, Klaipėda University academics, the local movements of cultural workers and public figures and theinitiatives launched by them. As regards the scholarly and information aspect, due to the pool of intellectual and financial resources, Vilnius played an important role. The scientific institutions of the capital city held a seminar and discus sion on The Relevance of Ieva Simonaitytė, and the texts of the reports of the participants were published in the journal Colloquia (2017, Nr. 38); the Vilnius University Academic Publishers published a book of evidential texts and reminiscences, I’m Evė, Daughter of Etmė. Lithuanian Radio and Television released a documentary Ieva Simonaitytė and a radio version of the novel Vilius Karalius; they are professional and powerful, unfortunately, somewhat belated as they were shown at the end of the anniversary year. The program did not contain any long-term projects: the major novels and autobiographical books by Simonaitytė were not republished; compilation of the home library catalogue and the author’s bibliography was not undertaken; the publication of the epistolary heritage, especially in the German language, was not continued; and a conference on the up-to-date analysis and assessment of the personality and her work was not held. The public was disappointed by the dire state of the Ieva Simonaitytė memorial museum in the town of Priekulė and failure to include it in to the activities of promoting her creative heritage. The Lithuanian general education schools have a problem too: the writer‘s literary works had been removed from their curricula for 20 years. When it was included into them again in 2016, teachers were faced with difficulties due to the lost experience and methods, the inability to convey the national, moral and social problems raised in the novels, the exceptional qualities of her characters, and the powerful suggestibility of Simonaitytė’s narratives. During discussions, the duty to fulfil the writer’s will was stressed: to move her remains from Vilnius to the garden at her memorial museum in Priekulė. To realize these tasks, it is necessary to prepare a long-term (for the duration of several years) program of commemorating Simonaitytė‘s work. Her novels are still relevant today as it was witnessed by a piece of investigative journalism: while celebrating the centenary of the restoration of Lithuania‘s independence, in the list of the Hundred of Centenary Books rated by a public opinion poll, the most important books of the writer were placed sixth and seventh.